2020
DOI: 10.1055/s-0041-1723104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hyperglycemia/Secondary Diabetes in Women who have Undergone Curative Chemotherapy for Breast Cancer: First Study from India

Abstract: Purpose Development of cancer chemotherapy treatment-induced hyperglycemia/ diabetes (secondary diabetes) is a major problem and has never been reported from India. The present study was planned to ascertain this in women undergoing curative chemotherapy for their breast cancer. Materials and Methods This was a retrospective chart-based study and was conducted in a cancer specialty hospital. The information on women who were nondiabetic at the start of the treatment was collected from the files. Details on can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…7 Our observations of the study suggested that by the end of the radiation treatment (which is the modality adopted after completion of surgery and chemotherapy), 24.89% were prediabetic, 10.97% were diabetic after being in the prediabetic stage, 8.22% became diabetic without going through a prediabetic stage, and only 55.91% did not develop either per diabetic or diabetic condition. 7 A strong correlation was also observed between the development of secondary hyperglycemia/diabetes and prediabetes with body mass index (BMI) and age. 7 From a biochemical perspective, accumulating evidence from innumerable clinical observations have conclusively shown that chronic inflammation plays a central role in the development and progression of both diabetes and cancer.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…7 Our observations of the study suggested that by the end of the radiation treatment (which is the modality adopted after completion of surgery and chemotherapy), 24.89% were prediabetic, 10.97% were diabetic after being in the prediabetic stage, 8.22% became diabetic without going through a prediabetic stage, and only 55.91% did not develop either per diabetic or diabetic condition. 7 A strong correlation was also observed between the development of secondary hyperglycemia/diabetes and prediabetes with body mass index (BMI) and age. 7 From a biochemical perspective, accumulating evidence from innumerable clinical observations have conclusively shown that chronic inflammation plays a central role in the development and progression of both diabetes and cancer.…”
Section: Introductionmentioning
confidence: 85%
“…7 A strong correlation was also observed between the development of secondary hyperglycemia/diabetes and prediabetes with body mass index (BMI) and age. 7 From a biochemical perspective, accumulating evidence from innumerable clinical observations have conclusively shown that chronic inflammation plays a central role in the development and progression of both diabetes and cancer. [19][20][21][22] Reports suggest that when compared with the nondiabetic population, the incidence of gastric, liver, pancreatic, colorectal, urinary tract, breast, and female reproductive cancers is high in type II diabetes, and is accompanied by higher mortality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations